Protein modification with ISG15 blocks coxsackievirus pathology by antiviral and metabolic reprogramming - Kespohl, Meike; Bredow, Clara; Klingel, Karin; Voß, Martin; Paeschke, Anna; Zickler, Martin; Poller, Wolfgang; Kaya, Ziya; Eckstein, Johannes; Fechner, Henry; Spranger, Joachim; Fähling, Michael; et al. (Science advances, 2020)
Protein modification with ISG15 (ISGylation) represents a major type I IFN-induced antimicrobial system. Common mechanisms of action and species-specific aspects of ISGylation, however, are still ill defined and controversial. We used a multiphasic coxsackievirus B3 (CV) infection model with a first wave resulting in hepatic injury of the liver, followed by a second wave culminating in cardiac damage. This study shows that ISGylation sets nonhematopoietic cells into a resistant state, being indispensable for CV control, which is accomplished by synergistic activity of ISG15 on antiviral IFIT1/3 proteins. Concurrent with altered energy demands, ISG15 also adapts liver metabolism during infection. Shotgun proteomics, in combination with metabolic network modeling, revealed that ISG15 increases the oxidative capacity and promotes gluconeogenesis in liver cells. Cells lacking the activity of the ISG15-specific protease USP18 exhibit increased resistance to clinically relevant CV strains, therefore suggesting that stabilizing ISGylation by inhibiting USP18 could be exploited for CV-associated human pathologies. - Protein modification with ISG15 acts cooperatively with IFIT proteins and preserves glucose homeostasis. - Protein modification with ISG15 acts cooperatively with IFIT proteins and preserves glucose homeostasis.